Acoustic activity of some metals determined by the acoustic emission method - PILECKI, S.; SIEDLACZEK, J. (Archives of Acoustics, 1989)
Measurements of the acoustic emission (AE) count rate or count sum as well as the RMS value have been carried out by the use of the different AE analysers and the testing machines. Specimens of the Armco iron, 45 steel, 45 HNMFA steel, bearing steel ŁH15, beryllium bronze BB2 and the alloy of the maraging type N18K9M5T and PA2N alloy have been tested. Two kinds of specimens of St9OPA carbon-manganese steel have been tested, too: from new railway rails and from the 10-th year long exploited rails. AE characteristics and the results of the Kaiser and Bauschinger effect measurements have been presented.